choA+B+C=0 CMR:a^3+b^3+c^3=3abc cmr:a^2+b^2+c^2=2(a^4+b^4+c^4)
a,cho (a+b+c)^2 =3(ab+ac+bc)
cmr:a=b=c
b,Cho(a-b)^2+(b-c)^2+(c-a)^2 +4(ab+bc+ca)=4(a^2+b^2+c^2)
cmr:a=b=c
a) \(\left(a+b+c\right)^2=3\left(ab+bc+ac\right)\)
\(a^2+b^2+c^2+2ab+2ac+2bc-3ab-3ac-3bc=0\)
\(a^2+b^2+c^2-ab-ac-bc=0\)
\(2\left(a^2+b^2+c^2-ab-ac-bc\right)=0\)
\(2a^2+2b^2+2c^2-2ab-2ac-2bc=0\)
\(\left(a^2-2ab+b^2\right)+\left(a^2-2ac+c^2\right)+\left(b^2-2bc+c^2\right)=0\)
\(\left(a-b\right)^2+\left(a-c\right)^2+\left(b-c\right)^2=0\)
\(\Rightarrow a=b=c\left(đpcm\right)\)
\(CMR:a^3+b^3+c^3-3abc=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ac\right)\)
\(a^3+b^3+c^3-3abc\)
\(=\left(a^3+3a^2b+3ab^2+b^3\right)+c^3-\left(3a^2b+3ab^2+3abc\right)\)
\(=\left(a+b\right)^3+c^3-3ab\left(a+b+c\right)\)
\(=\left(a+b+c\right)\left[\left(a+b\right)^2-\left(a+b\right)c+c^2\right]-3ab\left(a+b+c\right)\)
\(=\left(a+b+c\right)\left(a^2+b^2+2ab-ac-bc+c^2-3ab\right)\)
\(=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-ac-bc\right)\)\(\left(đpcm\right)\)
\(a^3+b^3+c^3-3abc\)
\(=\left(a+b\right)^3+c^3-3a^2b-3ab^2-3abc\)
\(=\left(a+b\right)^3+c^3-3ab\left(a+b+c\right)\)
\(=\left(a+b+c\right)\left(\left(a+b\right)^2-c\left(a+b\right)+c^2\right)-3ab\left(a+b+c\right)\)
\(=\left(a+b+c\right)\left(\left(a+b\right)^2-c\left(a+b\right)+c^2-3ab\right)\)
\(=\left(a+b+c\right)\left(a^2+b^2+2ab-ac-bc+c^2-3ab\right)\)
\(=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)\)
cho a^3+b^3+c^3=3abc .cmr:a+b+c=0 hoặc a=b=c
cho a+b+c=0
cmr:a^3+b^3+c^3=3abc
Ta có :
Giả thuyết : a + b + c = 0
(a + b + c)3 = 0
a3 + b3 + c3 + 3.(a + b)(b + c)(c + a) = 0
Từ a + b + c = 0
=> \(\hept{\begin{cases}a+b=-c\\b+c=-a\\c+a=-b\end{cases}}\)
=> a3 + b3 + c3 + 3.(-c)(-a)(-b) = 0
=> a3 + b3 + c3 = 3abc
1.cho x,y thỏa mãn: ax+by=c,bx+cy=a,cx+by=b
CMR:a^3+b^3+c^3=3abc.
2.cho a,b,c khác 0 sao cho:ay-bx/c=cx-az/b=bz-cy/a
CMR:(ax+by+cz)=(x^2+y^2+z^2)(a^2+b^2+c^2)
\(1.\)
Theo đề ra, ta có:
\(ax+by=c\)
\(bx+cy=a\Leftrightarrow ax+by+bx+cy+cx+ay=c+a+b\)
\(cx+by=b\)
\(\Leftrightarrow x\left(a+b+c\right)+y\left(a+b+c\right)=a+b+c\)
\(\Leftrightarrow\left(x+y-1\right)\left(a+b+c\right)=0\)
Ta có: \(x,y\)thỏa mãn \(\Rightarrow a+b+c=0\Rightarrow a+b=\left(-c\right)\)
Khi đó ta có:
\(a^3+b^3+c^3=a^3+3ab\left(a+b\right)+b^3-3ab\left(a+b\right)+c^3\)
\(\Leftrightarrow\left(a+b\right)^3-3ab\left(a+b\right)+c^3=\left(-c\right)^3-3ab\left(-c\right)+c^3=3abc\)\(\left(đpcm\right)\)
Đặt: \(\frac{ay-bx}{c}=\frac{cx-az}{b}=\frac{bz-cy}{a}=G\)
\(\Rightarrow G=\frac{cay-cbx}{c^2}=\frac{bcx-baz}{b^2}=\frac{abz-acy}{a^2}\)
\(\Rightarrow G=\frac{cay-cbx+bcx-baz+abz-acy}{c^2+b^2+a^2}\)
\(\Rightarrow G=0\)
\(\Rightarrow\left(ay-bx\right)^2=\left(cx-az\right)^2=\left(bz-cy\right)^2=0\)
\(\Rightarrow\left(a^2+b^2+c^2\right)\left(x^2+y^2+z^2\right)=\left(ax+by+cz\right)^2\)
giai,cho,minh,bai,nay,di cho,a,b,c>=0.CMR:a^3+b^3+c^3>=3abc
a+b+c=0
a+b=-c
(a+b)^3=(-c)^3
a^3+3a^2b+3ab^2+b^3=(-c)^3
a^3+b^3+c^3=-3a^2b-3ab^2
a^3+b^3+c^3=-3ab(-c)
a^3+b^3+c^3=3abc
cho a,b,c>0.CMR:a^3/b+b^3/c+c^3/a>=a^2+b^2+c^2
a/(1+a)+2b/(1+b^2)+3c/(1+c^3)+4d/(1+d^4)+5e/(1+e^5) ≤1. CMR:a*b^2*c^3*d^4*e^5
Câu hỏi của Min - Toán lớp 9 - Học toán với OnlineMath
\(Cho:a+b+c=\frac{3}{2}.CMR:a^2+b^2+c^2\ge\frac{3}{4}\)